ANALISISI PENGELOLAAN DAN PEMANFAATAN DANA KAPITASI JAMINAN KESEHATAN NASIONAL PADA FASILITAS KESEHATAN TINGKAT PERTAMA MILIK PEMERINTAH (Study Pada Puskesmas Parigi Kabupaten Parigi Moutong) - Hi. Harbing, Hasmawati (Katalogis, 2018)
The study is analyzing the proses of budgeting, implementation and management, accountability, control and utilization, and anstacles in the managementand utilization of national health insurance capitation funds in community health center in Parigi in 2016. Type of study and data analysis is qualitative. Data collecting methods consist of in-depth interview, observation, and document review. Informants consist of 7 people who take part in the management and utilization of national health insurance capitation funds in Parigi’s health center, the key informant is the head of Health Departement in Parigi Moutong Regency. The result shows that the management of capitation funds of national health insurance has been implemented in accordance with the applicable laws and regulation, but there is a delay in reporting and and the accountablility of the clinic. This affect the delay in the issuance of SP3B dan SP2B, which also affects in the financial reporting delays. The utilization of capitation fund of national health insurance based on the Regents’ letter and regulations has been utilized 70% for service, 10% for medicine, BHP and medical devices, and 20% for operational feels. The amount of services feel paid to employees is based on the points collected. These determined by their presence, type of their work, and employment status. Utilization of operational costs affects by the limited resources, delays in planning, and expenditure of operasional costs that are considered difficult.